2019
DOI: 10.1111/jan.14085
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation exposure to the head is higher for scrub nurses than cardiologists during cardiac angiography

Abstract: Aims This study aimed to compare the head dose of a cardiologist to scrub and scout nurses during cardiac angiography. Design A correlational longitudinal quantitative design was used to examine the relationship between the variable of occupational dose to the medical operator when compared with the dose to the scrub and scout nurses. Methods A quantitative analysis was performed on data collected during coronary angiograms (N = 612) for one cardiologist and 22 nurses performing either the scrub or scout role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…BMI was found to affect dose levels to staff. This is unsurprising as the greater thickness of tissue an X-ray beam has to traverse, the higher number of X-rays are required, with a proportionally more substantial amount of scattered radiation incident on staff, which has been demonstrated previously 28 . When relatively large volumes of contrast were used, this was also shown to alter the trends of occupational dose as a predictor of temple dose, and this effect is understandable as larger volumes of contrast administered during an angiogram may be an indicator of greater procedural complexity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…BMI was found to affect dose levels to staff. This is unsurprising as the greater thickness of tissue an X-ray beam has to traverse, the higher number of X-rays are required, with a proportionally more substantial amount of scattered radiation incident on staff, which has been demonstrated previously 28 . When relatively large volumes of contrast were used, this was also shown to alter the trends of occupational dose as a predictor of temple dose, and this effect is understandable as larger volumes of contrast administered during an angiogram may be an indicator of greater procedural complexity.…”
Section: Discussionmentioning
confidence: 85%
“…Scrub nurses are generally positioned further away from the most significant source of x-ray scatter, which suppositionally reduces their level of exposure compared to the doctor. Still, it has been reported that nursing staff may be exposed to higher levels of radiation than the doctor due to the shelter provided by the CMLS 28 30 , and this may be a contributing factor in the increased dose to scrub nurses. The presence of the X-ray detector has also been identified as providing an incidental protective barrier to doctors’ heads by absorbing X-ray photons, depending on the position of the doctor 18 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that if the movable lead shield is located directly in front of the fluoroscopic operator, it may afford protection only to that person. Hence, although the scrub nurse is positioned further away from the maximum area of scattered radiation, the absence of a physical barrier may result in a higher dose than the operator[ 39 ]. Another possible reason for increased dose during diagnostic coronary angiography is the inclusion of cases performed by non-interventional cardiologists, who may be less aware of radiation minimization strategies, leading to increased patient and staff dose.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 21 It has been previously reported that scrub or assistant dose is lower than that of the cardiologist ( table 6 ), 22 but this study has demonstrated a higher average dose received by the scrub nurse compared to the cardiologist, confirming the previous results published by our group. 23 This is postulated to be a result of the positioning of the ceiling-mounted lead directly in front of the cardiologist, providing a protective effect for them, but not staff adjacent to them. 23 Given the greater number of procedures, a nurse is typically involved in compared with a dr, this is cause for concern.…”
Section: Discussionmentioning
confidence: 99%
“… 23 This is postulated to be a result of the positioning of the ceiling-mounted lead directly in front of the cardiologist, providing a protective effect for them, but not staff adjacent to them. 23 Given the greater number of procedures, a nurse is typically involved in compared with a dr, this is cause for concern. Procedures performed on the angiographic system without the dose reducing software was associated with a significant increase in dose to staff, which has been demonstrated previously.…”
Section: Discussionmentioning
confidence: 99%